1987
DOI: 10.1128/jvi.61.4.1266-1270.1987
|View full text |Cite
|
Sign up to set email alerts
|

Course and extent of variation of equine infectious anemia virus during parallel persistent infections

Abstract: Comparisons of peptide and oligonucleotide maps of glycoproteins and RNA from nine isolates of equine infectious anemia virus (EIAV) that were generated during parallel infections of two Shetland ponies revealed that each isolate was structurally unique. Each EIAV isolate contained a unique subset of variant peptides, oligonucleotides, or both, indicating that structural variation in EIAV is a random and noncumulative process and that a large spectrum of possible EIAV variants can be generated in infected anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 16 publications
(25 reference statements)
2
22
0
Order By: Relevance
“…3]). These results are not surprising since differences in the tryptic glycopeptide maps among various EIAV isolates have been noted previously (33,38), and sequence analysis of EIAV and other lentiviruses has yielded similar changes in potential N-glycosylation sites (4,5,22,28,30). The addition of a potential N-glycosylation site within the PND of EIAV PV could account, in part, for its altered neutralization properties as described previously (37).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…3]). These results are not surprising since differences in the tryptic glycopeptide maps among various EIAV isolates have been noted previously (33,38), and sequence analysis of EIAV and other lentiviruses has yielded similar changes in potential N-glycosylation sites (4,5,22,28,30). The addition of a potential N-glycosylation site within the PND of EIAV PV could account, in part, for its altered neutralization properties as described previously (37).…”
Section: Resultssupporting
confidence: 75%
“…Sequence diversity in the env gene of the EIAV PV stock was low and was only slightly higher in the ponies infected with EIAV PV . While the former result is likely due to the fact that EIAV PV is a biological clone (37), the latter finding was somewhat surprising since previous studies have demonstrated rapid variations in the antigenic (14,33,38) and pathogenic (27) properties of EIAV during persistent infections in Shetland ponies. In fact, the predominant virus isolates from successive disease episodes separated by as few as 14 days have been shown to contain different gp90 and gp45 peptide maps (27,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations